Implementation of electronic charting is not associated with significant change in physician productivity in an academic emergency department. Issue 2 (26th June 2018) - Sarangarm, Dusadee; Lamb, Gregory; Weiss, Steven; Ernst, Amy; Hewitt, Lorraine
Abstract: Objectives: To compare physician productivity and billing before and after implementation of electronic charting in an academic emergency department (ED). Materials and methods: This retrospective, blinded, observational study compared the 6 months pre-implementation (January to June 2012) with the 6 months post-implementation 1 year later (January to June 2013). Thirty-one ED physicians were recruited, with each physician acting as his/her own control in a before-after design. Productivity was measured via total number of encounters and "productivity index" defined as worked relative value units divided by the clinical full-time equivalent. Values for charges, encounters, and productivity index were determined during each study period and separately for procedures, observational stays, and critical care. Results: No differences were found for total productivity index per month (758 [623-876] pre-group vs. 756 [673-886] post-group; P = 0.30). There was, however, a 9% decrease in total encounters per month (138 [101-163] pre-group vs. 125 [99-159] post-group; P = 0.01). Significant decreases were seen across all observation stay categories. Conversely, significant increases were seen across all critical care categories. There was no difference in total charges per month. Discussion: This is one of few studies to demonstrate minimal disruption in physician productivity after transitioning to electronic documentation. The reasons for these findings are likely multi-factorial. Conclusion: In this study, implementation of electronic charting was not associated with decreases in productivity or billing for total ED care, but may be associated with increases for critical care and decreases for observational stays.